Hubungan Curah Hujan dan Titik Panas (Hotspot) Kebakaran di Hutan Lindung Gambut (HLG) Londerang, Provinsi Jambi - Erianto Indra Putra; Rahmadika Fairuz Husni (Jurnal Silvikultur Tropika, 2021)
Jambi is one of the provinces that has high risk of forest fires in Indonesia.HLG Londerang is one of the protected peatland forests in Jambi that burned greatly in 2015. Precipitation become one of the climate factor that is affecting fires risk. This research is aimed to analyse the correlation between precipitation pattern peatland fires in HLG Londerang on 2013-2016. This research used hotspot data, precipitation, SPI (Standardized Precipitation Index), SOI (Southern Oscillation Index), and SSTA (Sea Surface Temperature Anomalies). Simple correlation test is used to acsess the relation between each parameters. This research showed that SPI-1 values could represent precipitation. In 2015, a great number of hotspot may relate to the El Nino event indicated by high positive value of SSTA and low SOI. There is a negative and weak correlation between precipitation and hotspot. Rainfall and SPI-1 has a positive and strong correlation. Combination of precipitation, SOI and SSTA is showing highest correlation with hotspot than other parameters. Keywords: fire, hotspot, precipitation, SOI, SPI, SSTA